Development of local politics in Thailand’s democracy - Arkamatheero, Phrasamu Arkom (Journal of MCU Phetchaburi Review, 2022)
Democracy Local Development uphold the principle of sovereignty as the people principles of rights and liberties of the people equality principle Principles of Governance by Law and Rule of Law and the majority principle A local organization with a status of “Government organization” to be a “social organization” capable of cooperating with all groups in the community. Accelerate the promotion of local people Participate in management, problem solving. Local politics is a political area involving the government. private business sector and the public sector All participate in the allocation of local valuables. by interacting with each other There may be cooperation, conflict and compromise. because local governments are like training institutions for people to have an understanding of the processes and mechanisms of political and governance in a democratic system; because it will help people to learn and gain a greater understanding of the political system.